Illicit Enrichment Dalam Upaya Pemberantasan Korupsi Di Indonesia - Mohamad Said Al-Hamid (Al-Mizan (e-Journal), 2022)
This study aims to elaborate on whether the criminalization of illicit enrichment has the potential to be an efficient and balanced action against corruption crimes, especially by public officials and to offer alternative formulations of illicit enrichment arrangements in corruption law as an effort to eradicate crime corruption in Indonesia. This study discusses the differences in the formulation of offenses in Article 2 Paragraph (1) and Article 3 of Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning Eradication of Corruption Crimes illicit enrichment in United Nations Convention Against Corruption (UNCAC) and offer alternative formulations of illicit enrichment in corruption laws. This study uses a normative legal research method with a statutory approach and a contextual approach. The results of the study show that Indonesia has ratified the concept of illicit enrichment in the UNCAC but has not regulated further illicit enrichment in its national law. Even though Indonesia has regulated its provisions in Article 2 and Article 3 of the Corruption Law, these provisions still have weaknesses and have not accommodated the concept of illicit enrichment contained in the UNCAC. Therefore, in the following discussion, the authors offer the illicit enrichment offense formulation as an effort to eradicate corruption in Indonesia.